2015
DOI: 10.1007/s11250-015-0873-9
|View full text |Cite
|
Sign up to set email alerts
|

Productive and income contributions of sheep, goat, and cattle, and different diversification schemes in smallholder production systems of Northern Patagonia, Argentina

Abstract: Wool production oriented sheep keeping is the most important rural activity in Patagonia, Argentina, followed by goat and at a lower extent cattle production. The existing perception on the smallholder production systems from most decision makers (e.g., policy) is that they are marginal, with low productivity and have negative returns. Since the Argentinean economic scenario has changed drastically in the last decade, the aim of this study was to analyze the economic and productive contribution of different li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 15 publications
0
13
0
5
Order By: Relevance
“…For example, a regional study covering 106 smallholder households in north Patagonia and its diversity of systems (Fig. 1) showed that livestock contribution to household income was greater than 96%, especially by sheep, and that a sharp decline of wool prices resulted in outmigration of 42% of the rural population in the 1990s (Villagra et al, 2015). Next to sheep, goat rearing is also common and it generally promotes the settlement of families in the driest areas of the region, where productivity is low and other farming activities are not possible.…”
Section: Diversity Of Pastoral Systems In Patagoniamentioning
confidence: 99%
“…For example, a regional study covering 106 smallholder households in north Patagonia and its diversity of systems (Fig. 1) showed that livestock contribution to household income was greater than 96%, especially by sheep, and that a sharp decline of wool prices resulted in outmigration of 42% of the rural population in the 1990s (Villagra et al, 2015). Next to sheep, goat rearing is also common and it generally promotes the settlement of families in the driest areas of the region, where productivity is low and other farming activities are not possible.…”
Section: Diversity Of Pastoral Systems In Patagoniamentioning
confidence: 99%
“…Por otro lado, el sur de la provincia de Neuquén, la denominada Línea Sur de Río Negro y el noroeste de Chubut presentan una matriz mixta de productores capitalizados y estancias de amplias superficies, con predominancia de sistemas ganaderos extensivos ovinos-bovinos, y familias ganaderas de pequeña escala y comunidades indígenas, con sistemas mixtos ovinos-caprinos-bovinos Golluscio et al 2010;Villagra et al 2015). En general, el sistema de pastoreo involucra distintos ambientes de pastizales, que son utilizados con pastoreo continuo o con una lógica móvil, pero en el marco de límites espaciales definidos bajo un uso predial.…”
Section: Una Aproximación a Los Territorios Pastoriles De La Patagoniaunclassified
“…Principio de producción agropecuaria. La ganadería extensiva de base pastoril es la principal actividad productiva, de la cual dependen economías locales por ingresos económicos, abastecimiento de alimentos y fuentes de trabajo (Andrade 2012;Villagra et al 2015). En muchas zonas, la actividad pastoril preserva recursos genéticos locales (Lanari et al 2008).…”
Section: Principios Para La Protección Biocultural De Territorios Pastorilesunclassified
See 1 more Smart Citation
“…In Mediterranean mountains, grassland ecosystems are extremely important as producers of many goods and services for society (provisioning, regulation, support, culture) and as contributors to the support of a rich biodiversity (Millennium Ecosystem Assessment, 2005;Raudsepp-Hearne et al, 2010;Bernués et al, 2014). Grasslands provide forage for large wild herbivores and for livestock, so they play a prominent role in the mountain economy and even in many country economy's (Villagrasa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%